Development and validation of an analytical method for determination of chlorpyrifos in coffee and soil grains (Research, Society and Development, 2019)
The use of agrochemicals in agriculture aiming at increasing productivity is still very intense in Brazil due to the efficiency of these substances in the control and combat of pests that plague the plantations. Currently, there is great concern about the presence of these residues in food and soils due to their indiscriminate use. Coffee is a widely consumed product in Brazil and its cultivation is characterized by the use of large quantities of agrochemicals. The objective of this work was to evaluate coffee and soil samples from the coffee crop of the Venda Nova do Imigrante/ES region in order to quantify the presence of the chlorpyrifos pesticide using the methods of extraction by QuEChERS and ESL-PBT and analysis by Gas Chromatography coupled with Mass Spectrometry (GC/MS). The methods QuEChERS and ESL-PBT were tested for the extraction of chlorpyrifos agrotoxic in samples of coffee beans and soil at a depth of 5 and 15 cm. The GC/MS analysis method was developed and validated and used to quantify possible residues in the samples analyzed. The analyzes were performed by fortification with 2,0 mL of a 40,000 mg.L-1 working solution prepared from the pesticide standard. However, for the analysis in the samples in question the method could not identify the presence of the same.